Tinjauan Komposisi, Warna Dan Bentuk Pada Hasil Lukis Dengan Media Payung Di Sanggar Lukis Qalam Jihad - Hilyati Iftinan Lubis; Agus Priyatno (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
This research aims to determine the ability to organize compositions, process colors, adjust colors, and determine the level of suitability of shapes in the results of paintings using umbrella media at the Qalam Jihad Painting Studio Pematangsiantar. This research uses a qualitative descriptive method, by researching a topic in a systematic, factual and accurate manner obtained from data collection in the field and carried out based on existing facts and characteristics. This research is to review the composition, color and shape of paintings using umbrella media by studio students aged 13-15 years. The composition aspect gets the lowest score and the color aspect gets the highest score. This can be seen from the good coloring and color combinations with dark and light on the objects and colors that are seen clearly and appropriately by the studio students. Based on this, it produces a higher color aspect than other aspects. The classification of the results of reviewing the composition, color and shape of paintings using umbrella media at the Qalam Jihad Pematangsiantar painting studio is that 7 students are categorized as good with a score of 241.4 to 266 and an average score of 80.5 to 88.6. 8 students were quite good with scores of 211.2 to 234.9 with an average score of 70.4 to 78.3.